1972
DOI: 10.1038/icb.1972.46
|View full text |Cite
|
Sign up to set email alerts
|

CONCENTRATIONS OF IMMUNOGLOBULIN IN MAMMARY SECRETION OF RUMINANTS DURING INVOLUTION WITH PARTICULAR REFERENCE TO SELECTIVE TRANSFER OF IgG1

Abstract: Summary Involution of the mammary gland was initiated by stopping milking in 8 cows in the eighth to tenth month of lactation, in 4 ewes which had been lactating less than 7 weeks and in a further 6 ewes lactating more than 12 weeks. In all animals the concentrations of immunoglobulins in the mammary secretion—IgG1, IgC2, IgA and IgM—increased as involution progressed. In the cows and in those ewes in early lactation there was a transitory increase in selective transfer of IgG1 during the initial phase of invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The concentration of all immunoglobulin classes, i.e. IgG 1 , IgG 2 , IgA and IgM, increase markedly by the first week of the dry period (Watson et al., 1972).…”
Section: Does Dry Period Length Affect Mammary Defence?mentioning
confidence: 99%
“…The concentration of all immunoglobulin classes, i.e. IgG 1 , IgG 2 , IgA and IgM, increase markedly by the first week of the dry period (Watson et al., 1972).…”
Section: Does Dry Period Length Affect Mammary Defence?mentioning
confidence: 99%
“…In other words an antigenic insult results in impairment of the selective transport mechanism, breaching of the epithelial barrier (which would otherwise discriminate in the transfer of protein into secretion) and allows leakage of interstitial fluid into the mammary secretion. It has been observed that following antigenic insult, when signs of acute inflammation have disappeared, but when milk production is still depressed, there appeatsto be an increase in the magnifude of the selective transfer ofIgG 1 into milk (Lascelles 1969;Harmon et al 1976)~_ This appears to be another example of the inverse relationship between selective transport of IgG 1 and de novo synthesis of milk constituents in the gland (Watson et al 1972).…”
Section: Immunological Protection Of the Mammary Gland Itselfmentioning
confidence: 99%
“…Those fractions containing protein were pooled according to their position on the optical density profile, concentrated by dialysis, and their antibody content determined using the above assay techniques. The presence of each class of immunoglobulin was detennined by double diffusion in agar against monospecific antiserum prepared as described by Watson, Brandon and Lascelles (1972).…”
Section: Antibody Fractionationmentioning
confidence: 99%